2009
DOI: 10.1080/13607860902749057
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract EGb 761®, donepezil or both combined in the treatment of Alzheimer's disease with neuropsychiatric features: A randomised, double-blind, exploratory trial

Abstract: These exploratory findings helped to develop three hypotheses that will have to be proven in further studies: (1) there is no significant difference in the efficiency between EGb 761(R) and donepezil, (2) a combination therapy will be superior to a mono-therapy with one of both substances and (3) there will be less side effects under a combination therapy than under mono-therapy with donepezil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 26 publications
0
51
0
2
Order By: Relevance
“…Eight studies were placebo controlled, while two studies were a head-to-head trial with donepezil as comparison group [50] or a triple-blind study with Gb, donepezil, and placebo [51]. The very different dosages of Gb and donepezil rendered meta-analytical examination unfeasible in the latter studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were placebo controlled, while two studies were a head-to-head trial with donepezil as comparison group [50] or a triple-blind study with Gb, donepezil, and placebo [51]. The very different dosages of Gb and donepezil rendered meta-analytical examination unfeasible in the latter studies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, additional approaches are needed, and should include drugs that target various components of the neurodegeneration cascade. For example, there is evidence suggesting that the combined administration of a acetylcholinesterase inhibitors and anti-oxidants (Formula F or Ginkgo biloba-EGb 761) can more effectively improve cognitive performance than either compound alone [261, 262]. Since NMDA can promote insulin resistance [263], and NMDA neurotoxicity can be attenuated or prevented by insulin stimulation [264].…”
Section: Mechanisms Of Brain Insulin/igf Resistance In Neurodegeneratmentioning
confidence: 99%
“…Another recent study found that Ginkgo biloba was beneficial on scores of neuropsychiatric impairment, including apathy and depression/dysphoria, compared to placebo in a sample of adults with dementia [22]. An additional study showed some improvement in ratings of depression and cognition after taking Ginkgo biloba in a sample of adults who had Alzheimer's [23]. Thus, our findings appear to support other research that Max Stress B, similar to other nutrients, has the ability to improve subjective ratings of mental health.…”
Section: Discussionmentioning
confidence: 99%